Crack growth and energy dissipation in paper. Issue 1 (December 2018) - Hanifpour, Maryam; Mäkinen, Tero; Koivisto, Juha; Ovaska, Markus; Alava, Mikko
Abstract Here, we follow the stable propagation of a roughening crack using simultaneously Digital Image Correlation and Infra-Red imaging. In a quasi-two-dimensional paper sample, the crack tip and ahead of that the fracture process zone follow the slowly, diffusively moving "hot spot" ahead of the tip. This also holds when the crack starts to roughen during propagation. The well-established intermittency of the crack advancement and the roughening of the crack in paper are thus subject to the dissipation and decohesion in the hot spot zone. They are therefore not only a result of the depinning of the crack in a heterogeneous material.